Prevalence of Dental Caries among School Going Children in Dolakha, Nepal - Mahanta, Swagat Kumar; Prajapati, Dilip; Khadka, Anisha; Ghosh, Snehashish; Ghimire, Usha; Shahi, Shirshak; Khimbaja, Alina (Journal of College of Medical Sciences-Nepal, 2023)
Introduction There is a significant prevalence and morbidity of dental caries due to a lack of health education and insufficient preventive measures and the health status of students is not satisfactory. A number oforal disorders are linked to chronic diseases, and poor oral health has a major negative impact on overall health. People's everyday lives and general well-being are significantly impacted by pain, issues with eating, chewing, smiling, and communication brought on by missing, discolored, and damaged teeth. The aim of the study was to assess dental caries status among age groups, 3-14 years based on government and private schools. Methods A cross-sectional comparative study done among 377 school going students age 3-15 years. Children from both private and public schools were included in the study. Dental caries status was assessed using the WHO oral health assessment form for children 2013. Results The overall caries prevalence among the study participants was 341 (90.2%). Dental caries varied among age groups. Males scored higher dental caries levels than females. The private school students (5.78 ± 4.69) showed significantly higher levels of dental caries than the government school students (5.01 ±4.61). Conclusions The caries prevalence is very high in the school children of Dolakha with the highest burden among middle childhood age group with high number of untreated caries which emphasizes the need for further intervention.